Anhedonia is a Symptom of Severe Depression and Generalized Anxiety Disorder - Akhmad Vauwaz Z H; Nur Azizah; Hafid Algristian (Yayasan Sinergi Kawula Muda, 2026)
Anhedonia, defined as the reduced ability to experience pleasure, is a core symptom of major depressive disorder (MDD) and is increasingly recognized as a transdiagnostic marker that bridges depressive and anxiety disorders. This report presents the case of a 16-year-old Indonesian girl who exhibited pervasive sadness, irritability, fatigue, and marked anhedonia characterized by complete disengagement from competitive swimming, a central aspect of her self-identity. Psychosocial stressors, including parental conflict and academic pressure, preceded the escalation of symptoms. Clinical assessment revealed a severe depressive episode, with a Hamilton Depression Rating Scale (HDRS) score of 24 and significant anhedonia confirmed by the Snaith–Hamilton Pleasure Scale (SHAPS). Neurological and laboratory examinations were unremarkable. The patient was diagnosed with severe MDD (F32.2) and comorbid generalized anxiety disorder (F41.1) according to PPDGJ-III and DSM-5 criteria. Treatment included sertraline (up to 50 mg/day), short-term clobazam, and supportive psychotherapy with family intervention. At four-week follow-up, depressive symptoms improved, accompanied by partial recovery of motivation and social engagement. This case highlights anhedonia as a clinically prominent and functionally impairing symptom in adolescent depression and anxiety. Beyond its emotional dimension, anhedonia reflects a disruption of reward processing that contributes to poor academic, social, and developmental outcomes. Routine assessment of anhedonia using structured instruments such as SHAPS and culturally sensitive interviews may improve diagnostic precision and guide personalized treatment. Early detection and integrative interventions—combining pharmacological, psychotherapeutic, and family-based approaches—are essential for optimizing recovery and preventing long-term disability in adolescent mood disorders.